Towards a better understanding of the psychosocial determinants associated with adults' use of smokeless tobacco in the Jazan Region of Saudi Arabia: a qualitative study - Ibtisam Moafa; Rik Crutzen; Bart van den Borne; Mohammed Jafer; Maan Shabi; Ahmed Al-khaldi; Ahmed Abu-Zawah; Hameed Al-jabri; Ismaeel Hedad (BMC, 2022)
Abstract Background Most diagnosed oral cancer cases in Saudi Arabia are in the Jazan region. A common type of smokeless tobacco "Shammah" is prevalent in this region. This study aimed to gain an in-depth understanding of the possible psychosocial determinants of Shammah consumption among adult Shammah users in Jazan region. Methods A qualitative study was conducted by means of one-on-one interviews among thirty adult Shammah users. Participants were recruited by means of a purposive sampling technique. Data were collected using a semi-structured interview guide utilizing face-to-face and phone-call interviews. Thematic analysis with hybrid approach was used to analyze the dataset. Results Twenty-four sub-codes within four overarching themes were generated. Participants revealed uncertainty related to Shammah composition, how to quit knowledge and Shammah prevention/cessation programs. Shammah use identified as a normal phenomenon in society. Its use was frequently reported in participants' close network but most users faced family and peers' disapproval. Some users expressed joy, happiness and focused when using Shammah. Others were disgusted or neutral. Many users believed Shammah causes cancer and tears oral tissues. Others believed it relieves toothache or has no effect. Majority of users were confident to quit and recalled some quitting aids. Toothache, craving, drinking tea and chewing Khat (leaves of Catha edulis plant that causes moderate euphoria) perceived to be triggers to use Shammah. Availability of Shammah, withdrawal symptoms, stress, lack of support, seeing others using Shammah, losing part of routine and toothache were barriers to quit. Conclusions Shammah use was associated with uncertainty about Shammah composition and quitting knowledge, social acceptability, influence from family/friends, a range of positive and negative attitudinal beliefs toward its use and high quitting efficacy beliefs. Future interventions targeting Shammah should address the acknowledged triggers and barriers in the present study including the dual use of Shammah and Khat.